The highest utilizers of care: Individualized care plans to coordinate care, improve healthcare service utilization, and reduce costs at an academic tertiary care center. Issue 7 (9th April 2015) - Mercer, Tim; Bae, Jon; Kipnes, Joanna; Velazquez, Maureen; Thomas, Samantha; Setji, Noppon
<x xml:space="preserve">Abstract</x> BACKGROUND High utilizers are medically and psychosocially complex, have high rates of emergency department (ED) visits and hospital admissions, and contribute to rising healthcare costs. OBJECTIVE Develop individualized care plans to reduce unnecessary healthcare service utilization and hospital costs for complex, high utilizers of inpatient and ED care. DESIGN Quality‐improvement intervention with a retrospective pre/post intervention analysis. SETTING Nine hundred twenty‐four–bed tertiary academic medical center. PATIENTS Twenty‐four medically and psychosocially complex patients with the highest rates of inpatient admissions and ED visits from August 1, 2012 to August 31, 2013. INTERVENTION A multidisciplinary team developed individualized care plans integrated into our electronic medical record (EMR) that summarize patient histories, utilization patterns, and management strategies. MEASUREMENTS Primary outcomes included inpatient admissions, ED visits, and corresponding variable direct costs 6 and 12 months after care‐plan implementation. Secondary outcomes include inpatient length of stay (LOS) and 30‐day readmissions. RESULTS Hospital admissions decreased by 56% (P < 0.001) and 50.5% (P = 0.003), 6 and 12 months after care‐plan implementation. Thirty‐day readmissions decreased by 66% (P < 0.001) and 51.5% (P = 0.002), 6 and 12 months after care‐plan implementation. ED visits, ED costs, and inpatient LOS did not significantly change. Inpatient variable direct costs were reduced by 47.7% (P = 0.001) and 35.8% (P = 0.052), 6 and 12 months after care‐plan implementation. CONCLUSIONS Individualized care plans developed by a multidisciplinary team and integrated with the existing healthcare workforce and EMR reduce hospital admissions, 30‐day readmissions, and hospital costs for complex, high‐utilizing patients. Journal of Hospital Medicine 2015;10:419–424. © 2015 Society of Hospital Medicine